P4 3 Lost In Space - Devenport, Hannah K; Bakrania, Roshni A; Hanna, Caitlin J R; Malkin, Oliver W B (Physics Special Topics, 2023)
We explore the journey to Alpha Centauri using 2 different spaceships, as in Netflix's series "Lost in Space". We find the Resolute has an average speed of 100c, while the Jupiter is much slower and has a journey time of 5.87 years. As a result of the high speed travel, the Jupiter experiences a time dilation of 3 years, a length contraction of 11.9 m, and is Doppler shifted into the ultraviolet spectrum.